Adipose Collagen Fragment: A Novel Adipose-Derived Extracellular Matrix Concentrate for Skin Filling. (24th November 2021) - Zhang, Yuchen; Zhang, Xiangdong; Jin, Xiaoxuan; Zhang, Pan; Liu, Kaiyang; Yao, Yao; Ru, Jiangjiang; Li, Yibao; Xu, Mimi; Lu, Feng; He, Yunfan; Gao, Jianhua
Abstract: Background: Skin filler is an option for treating skin aging and wrinkles; however, currently used fillers are limited by poor biocompatibility, rapid degradation, and possible hypersensitivity reactions. Autologous adipose tissue–derived products have been recognized as promising options for skin rejuvenation. Objectives: This study aimed to develop a novel adipose-derived product for skin filling. Methods: Adipose collagen fragment (ACF) was prepared through pulverization, filtration, and centrifugation. The macrography, structure, types of collagen, and cell viability of ACF were evaluated by immunostaining, western blotting, and cell culture assays. ACF, nanofat, and phosphate-buffered saline (9 spots/side, 0.01 mL/spot) were intradermally injected in the dorsal skin of 36 female BALB/c nude mice; the skin filling capacity and the collagen remodeling process were then investigated. Twenty-one female patients with fine rhytides in the infraorbital areas were enrolled and received clinical applications of ACF treatment. Therapeutic effects and patients' satisfaction scores were recorded. Results: The mean [standard deviation] yield of ACF from 50 mL of Coleman fat was 4.91 [0.25] mL. ACF contained nonviable cells and high levels of collagen I, collagen IV, and laminin. Fibroblasts and procollagen significantly increased in ACF and ACF-treated dermis ( P < 0.05). Overall, 85.7% of patients were satisfied with the therapy results, and no infections, injection site nodules, or other unwanted side effects were observed. Conclusions: ACF significantly improved dermal thickness and collagen synthesis and may serve as a potential autologous skin filler.